Prevention of school bullying as a factor in the safety of the educational environment - Krushelnitskaya, O.B.; Marinova, T.Y.; Orlov, V.A.; Slastina, V.B. (Sovremennaâ Zarubežnaâ Psihologiâ, 2025)
Context and relevance. School bullying is a significant factor in violating the safety of the educational environment. The article presents the features of modern school bullying, analyzes its main causes. Examples of the development and implementation of bullying prevention programs show their capabilities to improve the safety of the school educational environment. Objective. To analyze modern foreign means of preventing school bullying as a factor in the safety of the educational environment. Hypothesis. Prevention of bullying as a factor in the safety of the educational environment is implemented within the framework of programs for the development of communicative competence and emotional self-regulation of students, improvement of the psychological climate and organizational conditions of school functioning. Comprehensive programs covering all participants in the school educational process are most effective. Theoretical basis. The analysis presented in the article is based on foreign data published from 2021 to 2025 on the development and application of school bullying prevention programs as a means of improving the safety of the educational environment. Results. Anti-bullying programs tested in foreign schools are primarily aimed at correcting personal and group factors that contribute to the development of teenage bullying, which poses a threat to the safety of the educational environment. Preventive projects with varying degrees of success solve the problems of increasing the socio-psychological competence of participants in the school educational process, reducing bullying and victimization, improving the psychological climate, and developing a prosocial position in interpersonal relationships among students. Conclusions. The psychological safety of the educational environment can be significantly increased with the help of systematic measures to prevent school bullying, which are a set of organizational and psychological-pedagogical means of harmonizing the system of interaction of all its participants, mainly teachers, students and their parents. Контекст и актуальность. Школьный буллинг является значимым фактором нарушения безопасности образовательной среды. В статье представлены особенности современного школьного буллинга, проводится анализ его основных причин. На примерах разработки и реализации программ профилактики буллинга показаны их возможности для повышения безопасности школьной образовательной среды. Цель. Проанализировать современные зарубежные средства профилактики школьного буллинга как фактора безопасности образовательной среды. Гипотеза. Профилактика буллинга как фактора безопасности образовательной среды реализуется в рамках программ развития коммуникативной компетентности и эмоциональной саморегуляции учащихся, совершенствования психологического климата и организационных условий функционирования школ. Наиболее эффективны комплексные программы, охватывающие всех участников школьного образовательного процесса. Теоретическая основа. Приведенный в статье анализ опирается на опубликованные с 2021 по 2025 гг. зарубежные данные о разработке и применении программ профилактики школьного буллинга как средства повышения безопасности образовательной среды. Результаты. Апробированные в зарубежных школах антибуллинговые программы преимущественно нацелены на коррекцию личностных и групповых факторов, которые способствуют развитию подросткового буллинга, создающего угрозу безопасности образовательной среды. Профилактические проекты с различной успешностью решают задачи повышения социально-психологической компетентности участников школьного образовательного процесса, снижения буллинга и виктимизации, улучшения психологического климата, а также формирования у учащихся просоциальной позиции в межличностных отношениях. Выводы. Психологическая безопасность образовательной среды может быть существенно повышена с помощью систематических мер профилактики школьного буллинга, представляющих собой комплекс организационных и психолого-педагогических средств гармонизации системы взаимодействия всех ее участников, главным образом педагогов, учеников и их родителей.